The Effect of Transformational Leadership on Employee Performance Mediated by Organizational Climate - alfarisi, Muhammad syahrul islakh; Nurhasana, Siti; Arifiani, Ratya Shafira (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
This study aims to determine and analyze the effect of transformational leadership on employee performance with organizational climate as a mediating variable. The type of research used in this research is explanatory using a quantitative approach. The population of this study was employees of the Batu City Land Office. The sampling technique uses total sampling. The sample used was 50 respondents at the Batu City Land Office. The data collection method for this study used a questionnaire. The data analysis technique in this study used path analysis using the SmartPLS software. The results of the study show that transformational leadership has a positive effect on employee performance; Transformational leadership has a positive effect on organizational climate; Organizational climate has a positive effect on employee performance.